2022
DOI: 10.3390/s22218138
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment and Emotional Analysis of Risk Perception in the Herculaneum Archaeological Park during COVID-19 Pandemic

Abstract: This paper proposes a methodology for sentiment analysis with emphasis on the emotional aspects of people visiting the Herculaneum Archaeological Park in Italy during the period of the COVID-19 pandemic. The methodology provides a valuable means of continuous feedback on perceived risk of the site. A semantic analysis on Twitter text messages provided input to the risk management team with which they could respond immediately mitigating any apparent risk and reducing the perceived risk. A two-stage approach wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Hence, after a proper organization of the answers, they could be elaborated through data mining techniques [81]. Considering the type of data, clustering or natural language processing (NLP) techniques could be applied, as already reported in scientific literature for other purposes (e.g., the sentiment analysis of perceptions about cultural heritage [82], occupational risk assessment [83,84]).…”
Section: Advantagesmentioning
confidence: 99%
“…Hence, after a proper organization of the answers, they could be elaborated through data mining techniques [81]. Considering the type of data, clustering or natural language processing (NLP) techniques could be applied, as already reported in scientific literature for other purposes (e.g., the sentiment analysis of perceptions about cultural heritage [82], occupational risk assessment [83,84]).…”
Section: Advantagesmentioning
confidence: 99%
“…The authors suggested that the open-source intelligence company involved in this project must understand its data holdings and comply with General Data Protection Regulation obligations. Also, many researchers (for example [81][82][83][84][85]), used OSINT methods and tools for emotional analysis, risk perception and mental health analysis during COVID-19 pandemic. This research was mainly based on social media analysis.…”
Section: Osint Research Opportunities and Solutionsmentioning
confidence: 99%
“…Sentiment analysis (SA) is one of the sections that belong to the NLP field [ 11 ] and is responsible for designing and applying models, techniques, and approaches to identify whether a text deals with objective or subjective information [ 55 ] and, in the last case, to identify whether that information was expressed in a negative, neutral, or positive manner [ 56 ] as well as whether it is strong or weak [ 26 ]. The SA method is used in many fields, especially in social media [ 57 ], such as classifying users’ opinions on social media posts [ 58 , 59 ], or knowing the tendencies of the masses in elections and predicting the final results, in addition to controlling public opinion by understanding the public’s attitudes by analyzing users’ opinions about certain situations [ 32 ].…”
Section: Background Of Studymentioning
confidence: 99%